Effect of reacting gas on the fluidic thrust vectoring of an axisymmetric nozzle - Chouicha, Rachid; Sellam, Mohammed; Bergheul, Saïd (Propulsion and Power Research, 2020)
During the last years, several thrust control systems of aerospace rocket engines have been developed. The fluidic thrust vectoring is one of them; it is simple in design and offers a substantial gain in weight and in performance. Numbers of studies that deal with this subject are conducted on cold gas flow model. It can be expected that the thermophysical properties of the gases may affect considerably the flow behavior. Besides, the effects of reacting gases at high temperatures, under their effects all flow parameters like to vary. This study aims to develop a new methodology that allows studying and analyzing the fluidic thrust vectoring for a reacting gas, by taking into account the effects chemical reactions on the flow parameters, such as separation point, reattachment point downstream and pressure distribution upstream the injection port. In this study, the thrust vectorization implying reacting hot gases was carried out by considering a chemical reaction mechanism. Reported study is based on Arrhenius reaction mechanism specific for H2–O2 propellant configuration. The thermodynamic parameters of the flow are calculated within the combustion chamber and different sections of the supersonic part of the nozzle. The results show a good agreement for cold gas, and as expected à slight difference for hot reacting gases. In parallel, in order to give more credibility to our work a study was carried out by numerical simulation for supersonic reactive and perfect flows in order to analyze the results of the method developed. In this work, the CFD performance of the fluidic thrust vectoring, has been qualitatively and quantitatively analyzed. Schlieren visualization and wall pressure results are compared to analytical and experimental findings.